Investigating the heat tolerance and production performance in local chicken breed having normal and dwarf size - Ali Hassan Nawaz; Shudai Lin; Fujian Wang; Jiahui Zheng; Junli Sun; Weilu Zhang; Zhenhai Jiao; Zijing Zhu; Lilong An; Li Zhang (Animal, 2023)
Heat stress significantly impairs the growth performance of broilers, which causes serious losses to the poultry industry every year. Thus, understanding the performance of indigenous chicken breeds under such environment is crucial to address heat stress problem. The purpose of this study was to investigate the effects of heat stress (HS) on production performance, tissue histology, heat shock response (HSP70, HSP90), and muscle growth-related genes (GHR, IGF-1, and IGF-1R) of Normal yellow chicken (NYC) and Dwarf yellow chicken (DYC). Seventy-two female birds from each strain were raised under normal environmental conditions up to 84 days, with birds from each strain being divided into two groups (HS and control). In the HS group, birds were subjected to high temperature at 35 ± 1 °C for 8 h daily and lasted for a week, while in the control group, birds were raised at 28 ± 1 °C. At 91 days old, bird's liver, hypothalamus, and breast muscle tissues were collected to evaluate the gene expression, histological changes, and the production performance. The Feed intake, weight gain ratio, total protein intake and protein efficiency ratio showed a significant reduction in the treatments (P < 0.01) and treatment × strain interaction (P < 0.05) with breast muscle rate significantly reducing among the treatments (P < 0.01) after 7 days of HS. Correspondingly, total abdominal fat showed significant change among treatment and strain (P < 0.01, P < 0.05), respectively. Besides, HS markedly upregulated the mRNA expression of HSP70 and HSP90 in the pectoralis major of both chicken strains, but no significant increase (P < 0.05) was found in mRNA expression of HSP90 in liver and hypothalamus tissues of both chicken strains. Moreover, HS significantly upregulated (P < 0.05) the expression of lipogenic genes (FASN, ACC) in liver tissues of NYC, while mRNA expression of these genes showed no variation in DYC. Similarly, HS downregulated the mRNA expression of muscle growth-related genes (GHR, IGF-1, and IGF-1R). Consequently, the histopathological analysis showed that histological changes were accompanied by inflammatory cell infiltration in liver tissues of both chicken strains; however, histopathological changes were more severe in NYC than dwarf chicken strain. Conclusively, this study depicted that the production performance and growth rate varied significantly between treatment and control group of NYC. However, heat treatment in DYC has not shown significant damaging consequences as compared to the control group that signifies the vital role of the dwarf trait in thermal tolerance.